(untitled) (Plant Tissue Culture and Biotechnology, 2017)
Genetic variation in 14 local Aman rice varieties of Bangladesh including single grain and multigrain rice was investigated at the DNA level by RAPD molecular typing. Fifteen random primers were initially screened against DNA from five individuals that generated highly reproducible RAPD fragments, which were then subjected to further population analysis. A total 191 RAPD fragments were generated with these primers and 153 (80.1%) were polymorphic, which indicated high level of polymorphism existed within these populations. The size of amplified fragments ranged between 450 and 6000 bp. Pair‐wise distance estimated the range of 0.03 to 0.59 between single and multigrain Aman rice varieties. Results illustrated the potential of RAPD markers to distinguish improved varieties and grain specificity at DNA level. Plant Tissue Cult. & Biotech. 27(2): 195-205, 2017 (December)